SIKAP MASYARAKAT TERHADAP PROGRAM PNPM MANDIRI DI DESA PULAU GAMBAR KECAMATAN SERBAJADI KABUPATEN SERDANG BEDAGAI - Risa Kartika Lubis (Jurnal Mantik Penusa, 2014)
A country if if want to want a smooth and sustainable development, it must start from the rural areas in general. Speaking of the countryside we are actually talking about poverty and the background and how to combat it, when we talk about the problem of poverty and indolence, we face a very big and complex problem. To improve the effectiveness of poverty alleviation and job creation, the government launched the National Community Empowerment Program (PNPM) Mandiri starting in 2007. Through PNPM Mandiri, it was formulated again the mechanism of poverty reduction efforts involving community elements, from planning, implementation, to monitoring and evaluation. The purpose of this study is to determine the attitudes of the community towards the program of PNPM Mandiri in the research area and the impact of PNPM Mandiri program on the socio-economic community in Pulau Pulau Pulau Singkajadi Serdang Bedagai district. This type of research is purposive research. The questionnaires were distributed by purposive sampling to the sample of the people who felt the assistance from the PNPM Mandiri program with the number of samples of 30 people on the island of Pulau Gambar. The results of this study indicate that the attitudes of the community towards the PNPM program provided by the government are positive, because it impacts both to the community and in accordance with the needs of the community in work. Socioeconomic impacts on PNPM Mandiri program on Social Differences Traveling to other areas / villages, Holding community meetings in relation to the PNPM Mandiri program, Conducting discussions among other villagers / other villages in relation to the PNPM Mandiri program, there are significant differences before and after the existence of PNPM Mandiri program. On Economic Differences Revenue, capital, number of jobs, number of working hours there are significant differences before and after the existence of PNPM Mandiri program. Only the number of working family members does not differ significantly between the number of family members working before and after the PNPM Mandiri program.Keywords: community attitude, socio-economic impact on PNPM Mandiri program.